Cognitive emotion regulation, anxiety, and depression in infertile women: a cross-sectional study - Fatemeh Foroudifard; Payam Amini; Behnaz Navid; Reza Omani-Samani; Mahdi Sepidarkish; Saman Maroufizadeh (Middle East Fertility Society Journal, 2020)
Abstract Background Cognitive strategies play an important role in the prevention of psychological disorders. The aim of this study was to examine the relationships of cognitive emotion regulation with anxiety and depression symptoms in a sample of infertile women in Iran. Results According to correlation analysis, all adaptive strategies (i.e., acceptance, positive refocusing, refocus on planning, positive reappraisal, and putting into perspective), except for Acceptance strategy, were indirectly related to both anxiety and depression symptoms. Conversely, four maladaptive strategies (i.e., self-blame, rumination, catastrophizing, and other-blame) were positively related to anxiety and depression symptoms. After controlling for demographic/infertility information, hierarchical regression analyses indicated that acceptance, rumination, and positive refocusing subscales were significantly associated with anxiety; and refocus of planning was related to depression. Conclusion In sum, cognitive emotion regulation strategies appeared to be related to anxiety and depression symptoms in women suffering from infertility. These results suggest the use of cognitive therapy to reduce the anxiety and depression in these women.